Precyclic-loading-induced stress corrosion cracking of pipeline steels in a near-neutral-pH soil environment - Wang, S-H; Chen, Weixing; King, Fraser; Jack, T. R; Fessler, R. R (Corrosion (Houston, Tex.), 2002)
NRC publication: No